Manufacturing method of fuel cell separator
By applying a negative bias voltage and low pressure sputtering, a uniform titanium layer is formed on the metal base material with uneven channels, addressing thickness disparities and improving corrosion resistance.
Patent Information
- Application Number
- JP2021176666
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-10-28
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2041-10-28
AI Technical Summary
The existing methods for forming a titanium layer on a metal base material with an uneven channel shape result in uneven thickness distribution, with the concave portions receiving a thinner layer than convex portions, leading to increased cost and potential corrosion issues.
A sputtering method is employed with a negative bias voltage of 150V or more and a sputtering gas pressure of 0.5 Pa or less to uniformly form a titanium layer on the metal base material, ensuring the thickness on concave and convex portions is more uniform and forming a flat structure without gaps.
The method achieves a uniformly thick titanium layer with excellent corrosion resistance, reducing the thickness disparity and enhancing the separator's durability against corrosive liquids.
Smart Images

Figure 0007613340000002 
Figure 0007613340000003 
Figure 0007613340000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for manufacturing a fuel cell separator. [Background technology]
[0002] A fuel cell comprises a structure in which a solid polymer electrolyte membrane is sandwiched between an anode electrode and a cathode electrode as a single cell. A fuel cell is also configured as a stack in which a plurality of the single cells are stacked via separators (also called bipolar plates) on which grooves that serve as flow paths for gases (hydrogen, oxygen, etc.) are formed. The output of a fuel cell can be increased by increasing the number of cells per stack.
[0003] Fuel cell separators also have the role of passing the generated electric current to the adjacent cell through the surface through which the cooling water flows, so the separator material that constitutes the separator must be electrically conductive.
[0004] For example, Patent Document 1 discloses a method for manufacturing a fuel cell separator in which a titanium film or a titanium nitride film is formed on a substrate. Specifically, Patent Document 1 discloses a method for manufacturing a fuel cell separator, which includes a first step of preparing a separator substrate, and a second step of forming a Ti film or a TiN film by a dry coating method while applying a bias voltage of a predetermined value or less to the surface of the separator substrate.
[0005] Patent Document 2 discloses a conductive member having a metal substrate layer and a conductive carbon layer containing conductive carbon, the conductive carbon layer being located on at least one of the main surfaces of the metal substrate layer, and wherein the D-band peak intensity (I D ) and G-band peak intensity (I G ) and the intensity ratio R(I D / I G) is 1.3 or more. Patent Document 2 discloses an embodiment in which a columnar intermediate layer is interposed between a metal substrate layer and a conductive carbon layer (e.g., claim 3), and titanium is cited as the material for the intermediate layer. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2008-34113 A [Patent Document 2] JP 2010-153353 A Summary of the Invention [Problem to be solved by the invention]
[0007] In a fuel cell separator, a metal substrate having an uneven flow path shape is used to form a groove that serves as a flow path. Here, the present inventors have found that when a titanium layer made of titanium is formed on a metal substrate having an uneven flow path shape by a sputtering method, a difference occurs between the film thickness of the titanium layer formed on the convex portion and the film thickness of the titanium layer formed on the concave portion. Specifically, the inventors have found that the film thickness of the titanium layer formed on the concave portion is smaller than the film thickness of the titanium layer formed on the convex portion. From the viewpoint of corrosion resistance, it is desirable to ensure that the film thickness of the titanium layer formed on the concave portion is also at least a certain value. However, if the film thickness of the titanium layer formed on the concave portion is increased, the film thickness of the titanium layer formed on the convex portion will also be larger than necessary, which will lead to an increase in costs. Therefore, there has been a demand for the development of a film forming method for a titanium layer that can bring the film thickness of the titanium layer formed on the concave portion closer to the film thickness of the titanium layer formed on the convex portion.
[0008] Therefore, an object of the present disclosure is to provide a method for manufacturing a fuel cell separator that can form a titanium layer more uniformly than conventional methods on a metal substrate having an uneven flow path shape. [Means for solving the problem]
[0009] As described above, the present inventors have found that when a titanium layer made of titanium is formed on a metal substrate having an uneven flow path shape by a general sputtering method, the thickness of the titanium layer formed on the concave portion is smaller than the thickness of the titanium layer formed on the convex portion. The sputtering method is usually a method in which a raw material as a target is blown onto the surface of the metal substrate to be coated by impact or the like under reduced pressure to physically form a thin film, but even in a reduced pressure state, sputtering gas is present in the atmosphere. There is a difference in distance to the target between the convex portion and the concave portion of the metal substrate, and until the raw material molecules reach the concave portion, there are more molecules that become obstacles by the difference compared to the convex portion. Therefore, it is presumed that the raw material molecules that reach the concave portion, especially the bottom of the concave portion, are fewer than the raw material molecules that reach the convex portion, and the thickness of the layer formed on the concave portion is smaller than the thickness of the layer formed on the convex portion. Note that this presumption does not limit the present embodiment.
[0010] Therefore, after extensive research, the inventors discovered that by forming a titanium layer by a sputtering method under specified conditions, the thickness of the titanium layer formed in the recessed portions can be made close to the thickness of the titanium layer formed in the protruding portions.
[0011] Therefore, an example of the embodiment is as follows.
[0012] (1) A method for manufacturing a fuel cell separator having a titanium layer made of titanium on a metal substrate having an uneven flow channel shape, comprising the steps of: The method includes the step of depositing a titanium layer on a metal substrate by a sputtering method in which a negative bias voltage is applied to the metal substrate; The sputtering gas pressure is 0.5 Pa or less, The method of manufacturing, wherein the negative bias voltage is 150V or more. (2) The manufacturing method described in (1), wherein the negative bias voltage is 150V or more and 1280V or less. (3) The manufacturing method according to (1) or (2), wherein the negative bias voltage is 150 V or more and 500 V or less. (4) The method according to any one of (1) to (3), wherein sputtering is carried out using a sputtering target containing titanium as a main component. (5) The manufacturing method according to any one of (1) to (4), wherein argon is used as a sputtering gas. (6) The method according to any one of (1) to (5), wherein the formed titanium layer has a flat structure and has no boundary or gap extending from the surface of the titanium layer to the surface of the metal substrate. (7) The method for producing a titanium layer according to any one of (1) to (6), wherein the ratio (B / A) of the thickness A of the titanium layer formed on the convex portions of the metal substrate to the thickness B of the titanium layer formed on the concave portions is 0.8 or more. (8) The method according to any one of (1) to (7), wherein the metal substrate is a stainless steel substrate. (9) The method according to any one of (1) to (8), further comprising the step of depositing a carbon layer made of carbon on the deposited titanium layer. Effect of the Invention
[0013] The present disclosure makes it possible to provide a method for manufacturing a fuel cell separator that can form a titanium layer more uniformly than in the past on a metal substrate having an uneven flow channel shape. [Brief description of the drawings]
[0014] [Figure 1A] 2 is a schematic cross-sectional view illustrating an example of a layer structure of a fuel cell separator according to the present embodiment. FIG. [Figure 1B] 2 is a schematic cross-sectional view illustrating an example of a layer structure of a fuel cell separator according to the present embodiment. FIG. [Figure 2A] 3A to 3C are schematic cross-sectional views illustrating examples of the shape of a fuel cell separator according to the present embodiment. [Figure 2B] 3A to 3C are schematic cross-sectional views illustrating examples of the shape of a fuel cell separator according to the present embodiment. [Diagram 3] 1 is a schematic cross-sectional view for explaining a configuration example of a fuel cell according to an embodiment of the present invention. [Figure 4] 1 is a SEM photograph of a cross section of separator E1 according to Example 1. [Diagram 5] 1 is a SEM photograph of a cross section of a separator C1 according to Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present embodiment is a manufacturing method for a fuel cell separator having a titanium layer on a metal substrate having an uneven flow path shape, the manufacturing method including a step of forming a titanium layer on the metal substrate by a sputtering method in which a negative bias voltage is applied to the metal substrate, the sputtering gas pressure being 0.5 Pa or less, and the negative bias voltage being 150 V or more.
[0016] According to this embodiment, a titanium layer can be formed more uniformly on a metal substrate having an uneven flow path shape than in the past. Also, according to this embodiment, a titanium layer having excellent corrosion resistance can be formed. The reason why the thickness of the titanium layer formed on the recessed portion can be made closer to the thickness of the titanium layer formed on the protruding portion is presumed as follows. The condition that the sputtering gas pressure is 0.5 Pa or less is considered to be due to the fact that the sputtering gas that is an obstacle to reaching the metal substrate is reduced, making it easier for the raw material molecules to reach the recessed portion, and the condition that the negative bias voltage is 150 V or more is considered to be due to the fact that the particles emitted from the sputtering target have high energy and can easily reach the recessed portion without changing their course direction even if they collide with the sputtering gas. Note that this embodiment is not limited by this presumption.
[0017] In addition, since fuel cell separators come into contact with low-pH generated water (corrosive liquid) containing chloride ions and fluoride ions during use, fuel cell separators are required to have excellent corrosion resistance. Therefore, the quality of the titanium layer formed on the metal substrate has been desired to be improved from the viewpoint of corrosion resistance. For example, in the case of a titanium layer having a columnar structure as described in Patent Document 2, there is a boundary or gap between the columns that leads to the metal substrate surface, and a corrosive liquid may penetrate through the boundary or gap and corrode the metal substrate. Surprisingly, it has been found that the titanium layer obtained by the manufacturing method according to this embodiment has a flat structure in which there is no boundary or gap from the titanium layer surface to the metal substrate surface as seen in the columnar structure, and therefore has excellent corrosion resistance. It is believed that by forming a titanium layer by the sputtering method under the conditions of this embodiment, the titanium particles move in the left and right directions after reaching the substrate and combine with nearby titanium particles to form a dense film. That is, the lower the sputtering gas pressure and the higher the negative bias voltage, the easier it is for the particles emitted from the sputtering target to reach the metal substrate with high energy, and they meet and bond with nearby titanium particles on the surface of the metal substrate to form a dense film, which is believed to be why the titanium layer has a flat structure that is denser than the columnar structure. Note that this embodiment is not limited by this assumption. The titanium layer produced by the above method has a flat structure and has excellent corrosion resistance because there is no boundary or gap that leads from the titanium layer surface to the metal substrate surface as seen in the columnar structure. Therefore, the manufacturing method according to this embodiment can form a titanium layer with excellent corrosion resistance.
[0018] The details of this embodiment will be described below.
[0019] The present embodiment relates to a method for manufacturing a fuel cell separator having a titanium layer made of titanium on a metal substrate having an uneven flow passage shape.
[0020] First, the configuration of a fuel cell separator and a fuel cell produced by a manufacturing method according to this embodiment will be described with reference to the drawings as appropriate.
[0021] FIG. 1A is a schematic cross-sectional view for explaining an example of the layer structure of the fuel cell separator according to the present embodiment. As shown in FIG. 1A, the fuel cell separator 1001 has a titanium layer 102 formed on a metal substrate 101. The titanium layer 102 may constitute the surface of the fuel cell separator by itself, or may exist as an intermediate layer, and other layers may be formed on the titanium layer 102. FIG. 1B is a schematic cross-sectional view for explaining an example of the layer structure of the fuel cell separator according to the present embodiment, and shows a fuel cell separator 1002 having a configuration in which a carbon layer 103 is formed as a conductive layer on the titanium layer 102. The titanium layer 102 is formed on at least one surface of the metal substrate 101, and may be formed on both surfaces.
[0022] 2A and 2B are schematic cross-sectional views showing examples of the shape of a metal substrate of a fuel cell separator. The shape of the metal substrate determines the shape of the fuel cell separator. The metal substrate 101a shown in FIG. 2A and the metal substrate 101b shown in FIG. 2B are each formed in a corrugated shape and have a repeated structure of recesses and protrusions. Both metal substrates have almost the same shape when viewed from the front side and the back side. As described later, the spaces of the recesses and the protrusions can function as flow paths for gas and cooling water. In this embodiment, when the separator is placed on a horizontal surface with the surface on which the titanium layer is formed facing up, the parts recessed downward can be understood as recesses, and the parts protruding upward can be understood as protrusions.
[0023] The shape of the metal base material 101a in Fig. 2A is not angular, and both the concave and convex portions have continuous round waves. The shape of the metal base material 101b in Fig. 2B is an approximately isosceles trapezoid, with flat crests and angular ends at equal angles. The metal base material is not particularly limited as long as it has a flow path shape consisting of a repeated structure of concaves and convex portions, that is, an uneven flow path shape.
[0024] The fuel cell includes a stack of unit cells, each of which is made up of a power generating body and fuel cell separators disposed on both sides of the power generating body. A plurality of unit cells are stacked in a stacking direction, and each unit cell is electrically connected in series. FIG. 3 is a schematic cross-sectional view for explaining a configuration example of a fuel cell according to this embodiment, and is a cross-sectional view of a main part of a fuel cell 10 as an example. As shown in FIG. 3, the fuel cell 10 includes a plurality of unit cells 1, which are basic units, stacked. Each unit cell 1 is a solid polymer electrolyte fuel cell that generates an electromotive force by an electrochemical reaction between an oxidant gas (e.g., air) and a fuel gas (e.g., hydrogen). The unit cell 1 includes a membrane electrode & gas diffusion layer assembly (MEGA) 2 having gas diffusion layers (GDLs) 7 disposed on both sides, and a separator 3 in contact with the MEGA 2 so as to partition the MEGA 2. In this embodiment, the MEGA 2 is sandwiched between a pair of separators 3, 3.
[0025] The MEGA 2 includes a membrane electrode assembly (MEA) 4 and gas diffusion layers 7, 7 arranged on both sides of the MEA. The membrane electrode assembly 4 is composed of an electrolyte membrane 5 and a pair of electrodes 6, 6 joined to sandwich the electrolyte membrane 5. The electrolyte membrane 5 is, for example, a proton-conductive ion exchange membrane formed of a solid polymer material. The electrode 6 is, for example, formed of a porous carbon material supporting a catalyst such as platinum. The electrode 6 arranged on one side of the electrolyte membrane 5 functions as an anode, and the electrode 6 on the other side functions as a cathode. The gas diffusion layer 7 is formed of a conductive member having gas permeability. Examples of the conductive member having gas permeability include a carbon porous body such as carbon paper or carbon cloth, or a metal porous body such as a metal mesh or metal foam.
[0026] The MEGA 2 is the power generation part of the fuel cell 10, and the separator 3 is in contact with the gas diffusion layer 7 of the MEGA 2. When the gas diffusion layer 7 is not present, the membrane electrode assembly 4 is the power generation part, and in this case, the separator 3 is in contact with the membrane electrode assembly 4. Therefore, the power generation part of the fuel cell 10 includes the membrane electrode assembly 4, and is in contact with the separator 3.
[0027] The separator 3 is a plate-shaped member having a metal substrate (e.g., a stainless steel substrate). The metal substrate has excellent electrical conductivity and gas impermeability. In Fig. 3, the surface of the separator 3 on the power generation side is in contact with the gas diffusion layer 7 of the MEGA 2, and the other surface is in contact with another adjacent separator 3.
[0028] In Fig. 3, each separator 3 is formed in a corrugated shape, and has an uneven flow channel shape. The shape of the separator 3 in Fig. 3 is an isosceles trapezoid, the crest of the wave is flat, and both ends of the crest are angular with equal angles. Each separator 3 has almost the same shape whether viewed from the front side or the back side. The top of the separator 3 is in surface contact with one gas diffusion layer 7 of the MEGA2, and the top of the separator 3 is in surface contact with the other gas diffusion layer 7 of the MEGA2.
[0029] A gas flow path 21 defined between the gas diffusion layer 7 on one electrode (i.e., anode) 6 side and the separator 3 is a flow path through which a fuel gas flows, and a gas flow path 22 defined between the gas diffusion layer 7 on the other electrode (i.e., cathode) 6 side and the separator 3 is a flow path through which an oxidizer gas flows. When a fuel gas is supplied to one of the gas flow paths 21 facing each other via the cell 1 and an oxidizer gas is supplied to the gas flow path 22, an electrochemical reaction occurs in the cell 1, generating an electromotive force.
[0030] Furthermore, a certain cell 1 and another adjacent cell 1 are arranged with the anode electrode 6 and the cathode electrode 6 facing each other. Also, the top of the back side of the separator 3 arranged along the anode electrode 6 of a certain cell 1 is in surface contact with the top of the back side of the separator 3 arranged along the cathode electrode 6 of the other cell 1. A refrigerant (e.g., water) for cooling the cell 1 flows through a space (coolant flow path) 23 defined between the separators 3, 3 that are in surface contact between two adjacent cells 1.
[0031] In this embodiment, it is preferable that a titanium layer is formed on the surface of the separator facing the power generation section. As described above, the fuel cell separator is required to have excellent corrosion resistance because it comes into contact with low pH product water (corrosive liquid) containing chloride ions and fluoride ions during use. Therefore, it is preferable that a titanium layer is formed on the surface of the separator facing the power generation section.
[0032] As described above, in this embodiment, another layer may be formed on the titanium layer. The other layer may be appropriately selected from the viewpoint of improving electrical conductivity and / or corrosion resistance. As the other layer, a carbon layer made of carbon is preferably formed. The carbon layer made of carbon has excellent durability due to its high film strength, and can reduce the contact resistance of the separator due to its excellent electrical conductivity. In addition, the adhesion between the titanium layer and the metal substrate such as a stainless steel substrate and the adhesion between the titanium layer and the carbon layer are both good, so that the titanium layer can bond the carbon layer more firmly to the metal substrate, which leads to further improvement in the film strength of the carbon layer and can contribute to reducing the contact resistance of the separator. In addition, the corrosion resistance of the separator can be significantly improved by adding the corrosion resistance of the titanium layer having a flat structure obtained by this embodiment.
[0033] In this embodiment, the power generation section preferably includes a gas diffusion layer, and the carbon layer of the separator is preferably in contact with the gas diffusion layer of the MEGA serving as the power generation section.
[0034] The metal constituting the metal substrate is not particularly limited, but examples thereof include iron, aluminum, and alloys thereof. These materials can be preferably used from the viewpoints of mechanical strength, versatility, cost performance, ease of processing, and the like. The iron alloy may include stainless steel. In this embodiment, the metal substrate is preferably a stainless steel substrate. When the metal substrate is a stainless steel substrate, the electrical conductivity of the contact surface with the gas diffusion layer or the like can be sufficiently ensured. The stainless steel substrate is not particularly limited, but examples thereof include austenitic, ferritic, austenitic-ferritic two-phase, martensitic, and precipitation hardening substrates.
[0035] The thickness of the metal substrate is appropriately selected in consideration of ease of processing, mechanical strength, and improvement of battery energy density by thinning the separator, and is, for example, 0.05 to 1 mm. When the thickness is in this range, the demand for a lightweight and thin separator is easily satisfied, and the separator material has the strength and handleability.
[0036] The manufacturing method according to this embodiment includes a step of forming a titanium layer on a metal substrate by a sputtering method in which a negative bias voltage is applied to the metal substrate, the sputtering gas pressure being 0.5 Pa or less, and the negative bias voltage being 150 V or more.
[0037] This process allows the titanium layer to be formed uniformly on the metal substrate having an uneven flow path shape, with the thickness of the titanium layer formed on the recesses being close to the thickness of the titanium layer formed on the protrusions. Furthermore, the titanium layer formed in this process has a flat structure and has no boundaries or gaps extending from the titanium layer surface to the metal substrate surface as seen in a columnar structure, and therefore has excellent corrosion resistance.
[0038] The titanium layer is preferably deposited directly on a metal substrate, that is, in contact with the metal substrate (eg, a stainless steel substrate).
[0039] The thickness of the titanium layer is not particularly limited, but is, for example, 0.1 to 1000 nm, preferably 10 nm to 500 nm, and more preferably 30 to 300 nm.
[0040] The titanium layer is preferably made of substantially pure titanium, and the purity of the titanium is preferably 99% by weight or more, and more preferably 99.9% by weight or more.
[0041] The method for forming the titanium layer is not particularly limited as long as it is a sputtering method. Examples of the sputtering method include DC sputtering, RF sputtering, AC sputtering, DC magnetron sputtering, RF magnetron sputtering, ion beam sputtering, unbalanced magnetron sputtering (UBMS), dual magnetron sputtering, and ECR sputtering. Among these, it is preferable to use DC sputtering and unbalanced magnetron sputtering.
[0042] In the deposition of the titanium layer by sputtering in this process, the sputtering gas pressure is set to 0.5 Pa or less, and the negative bias voltage is set to 150 V or more. By depositing the titanium layer under such conditions, the titanium layer can be deposited on the metal substrate having an uneven flow path shape with reduced difference in thickness between the titanium layer deposited on the concave portions and the titanium layer deposited on the convex portions. In addition, a titanium layer having a flat structure with excellent corrosion resistance can be deposited.
[0043] The negative bias voltage applied to the metal substrate is 150V or more. By setting the negative bias voltage to 150V or more, the difference between the thickness of the titanium layer formed on the concave portion and the thickness of the titanium layer formed on the convex portion can be effectively reduced, and a titanium layer having a flat structure can be formed. The negative bias voltage applied to the metal substrate is preferably 200V or more, preferably 250V or more, and preferably 300V or more. The negative bias voltage applied to the metal substrate is preferably 1280V or less, preferably 1200V or less, preferably 1100V or less, preferably 1000V or less, preferably 900V or less, preferably 800V or less, preferably 700V or less, preferably 600V or less, and preferably 500V or less. By setting the negative bias voltage to 1280V or less, excessive reduction in film thickness can be avoided.
[0044] The sputtering gas pressure in the film formation process is 0.5 Pa or less. By setting the sputtering gas pressure to 0.5 Pa or less, the difference in thickness between the titanium layer formed on the concave portion and the titanium layer formed on the convex portion can be effectively reduced, and a titanium layer having a flat structure rather than a columnar structure can be formed. As described above, the flat structure has excellent corrosion resistance because there is no boundary or gap from the titanium layer surface to the metal substrate surface as seen in the columnar structure. The sputtering gas pressure is preferably 0.4 Pa or less, more preferably 0.3 Pa or less, more preferably 0.2 Pa or less, more preferably 0.1 Pa or less, and more preferably 0.08 Pa or less.
[0045] In the film-forming step, the ratio (B / A) of the thickness A of the titanium layer formed on the convex parts of the metal substrate to the thickness B of the titanium layer formed on the concave parts is preferably 0.8 or more, more preferably 0.85 or more, and even more preferably 0.9 or more. The thickness A of the titanium layer formed on the convex parts of the metal substrate can be obtained by measuring the thickness of the titanium layer at the top, which is the highest part of the convex parts. The thickness B of the titanium layer formed on the concave parts can be obtained by measuring the thickness of the titanium layer at the bottom, which is the lowest part of the concave parts. The thickness of the titanium layer can be obtained by observing the cross section of the separator by SEM or the like, and averaging the thicknesses of at least 10 points on the convex parts (or concave parts) in the cross section.
[0046] The sputtering target used is preferably made of titanium. The higher the purity, the more preferable, and the content of metal impurities is preferably less than 1% by weight, preferably less than 0.1% by weight, and more preferably less than 0.01% by weight.
[0047] The degree of vacuum in the deposition equipment before deposition was 3×10 -5 Pa or less, and 1×10 -5 It is preferable that the vacuum pressure is set to not more than 1 Pa. By setting the vacuum pressure at a lower pressure, residual gas is less likely to be mixed in as an impurity during film formation, improving the quality of the thin film.
[0048] The metal substrate may be pretreated before the deposition of the titanium layer. By carrying out the pretreatment of the metal substrate, it is possible to remove any impurities that may be a hindrance to adhesion on the surface of the metal substrate. Examples of pretreatment methods include reverse sputtering, acid treatment, and UV treatment, but reverse sputtering is preferred from the viewpoint of preventing re-adhesion of impurities after treatment. Reverse sputtering is a method of cleaning the surface by colliding plasma atoms with the metal substrate, not with the sputtering target, and with the metal substrate. By utilizing this mechanism, the substrate surface is cleaned and sent to the deposition chamber without exposure to the outside air, making it possible to deposit a film while maintaining the cleanliness of the substrate surface. In performing reverse sputtering, it is preferable to perform the treatment separately from the deposition chamber in order to prevent reverse sputtered impurities from adhering to the deposition chamber. For example, argon, nitrogen, oxygen, etc. can be used as the gas species for reverse sputtering.
[0049] The sputtering gas is not particularly limited, but may be, for example, argon, or a mixed gas containing argon.
[0050] The power density during discharge is 0.5W / cm 2 More than 20W / cm 2 It is preferable that the value is less than 1 W / cm 2 More than 10W / cm 2 The power density is calculated by dividing the power applied during discharge by the area of the sputtering target.
[0051] The distance from the sputtering target to the metal substrate is not particularly limited, but is, for example, 100 to 250 mm, and preferably 180 to 220 mm.
[0052] As described above, another layer may be formed on the titanium layer. The other layer may be appropriately selected from the viewpoint of improving electrical conductivity and / or corrosion resistance, and a preferred example of the other layer is a carbon layer made of carbon.
[0053] The carbon layer is made of carbon and is composed of a crystalline and / or amorphous structure, and may include a polycrystalline graphite structure. The carbon layer is preferably deposited directly on, i.e., in contact with, the titanium layer. The carbon layer is preferably the top layer of the separator. The carbon layer is substantially free of other materials such as resins.
[0054] The thickness of the carbon layer is not particularly limited, but is, for example, 0.1 to 1000 nm, preferably 10 nm to 500 nm, and more preferably 15 to 200 nm.
[0055] The method for forming the carbon layer is not particularly limited, and examples thereof include physical vapor deposition (PVD) methods such as sputtering or ion plating, or ion beam deposition methods such as filtered cathodic vacuum arc (FCVA). Among them, it is preferable to use the sputtering method or the ion plating method. Examples of the sputtering method include ion beam sputtering, DC sputtering, RC sputtering, magnetron sputtering, unbalanced magnetron sputtering (UBMS), dual magnetron sputtering, and ECR sputtering. Examples of the ion plating method include the arc ion plating method. In particular, it is preferable to use the ion plating method for forming the carbon layer, and it is preferable to use the arc ion plating method. According to these methods, it is possible to form a carbon layer with a low hydrogen content. As a result, it is possible to increase the ratio of bonds between carbon atoms (sp2 hybrid carbon), and excellent electrical conductivity can be achieved.
[0056] In addition, in the sputtering method, the film quality obtained can be controlled by controlling the bias voltage, etc. When forming a layer by the sputtering method, a negative bias voltage may be applied to the substrate during sputtering. This allows the layer to be formed densely and improves corrosion resistance. The magnitude of the negative bias voltage applied during the formation of the carbon layer is not particularly limited, but is, for example, 5 to 50 V, or 10 to 40 V.
[0057] In a fuel cell, fluoride ions are easily generated from a fluorine-based electrolyte resin such as a perfluorosulfonic acid polymer. Therefore, when a fuel cell uses a solid electrolyte membrane containing a fluorine-based electrolyte resin, the fuel cell separator of this embodiment is particularly useful. Examples of the fluorine-based electrolyte resin include perfluorosulfonic acid polymers, and specific examples include Nafion (trade name, manufactured by DuPont), Flemion (trade name, manufactured by Asahi Glass Co., Ltd.), and Aciplex (trade name, manufactured by Asahi Kasei Co., Ltd.). Among these, Nafion (trade name, manufactured by DuPont) is preferably used because of its excellent proton conductivity.
[0058] According to the present embodiment described above, a titanium layer can be formed on a metal substrate having an uneven flow path shape more uniformly than in the past, and a titanium layer having excellent corrosion resistance can be formed. EXAMPLES
[0059] The present embodiment will be described below using examples.
[0060] [Example 1] A stainless steel substrate (SUS304) with a concave-convex flow channel pattern was prepared as the metal substrate. The stainless steel substrate had a corrugated shape as shown in Figure 2A, and consisted of a repeated structure of concaves and convexities. The distance between the tops of two adjacent convexities was 1.3 mm, and the vertical distance (depth) between the bottom of the concave and the top of the convex was 0.5 mm.
[0061] Then, a titanium layer was formed on the stainless steel substrate using a sputtering device (product name: FC1500, manufactured by IHI Hauser Techno Coatings Co., Ltd.). Specifically, the stainless steel substrate was placed in the reaction vessel of the device, and then the reaction vessel was evacuated and heated by an internal heater. Next, the pure Ti cathode target used for sputtering was etched (cleaned) with plasma Ar gas. In addition, in order to remove the passivation present on the surface of the stainless steel substrate, the stainless steel substrate was etched with plasma Ar gas. Next, using the above-mentioned pure Ti cathode target, a titanium layer was formed by unbalanced magnetron sputtering under the following conditions. Next, a carbon layer was formed on the titanium layer by arc ion plating (AIP) under the following conditions to produce a separator E1.
[0062] (Titanium layer deposition conditions) Target film thickness: 150 nm Processing temperature: 140℃ Sputtering gas: Ar Sputtering gas flow rate: 380sccm Sputtering gas pressure: 0.5Pa Bias voltage: -150V Frequency: 40kHz Ti cathode output: 35kW Orbital speed: 0.5 rpm Distance between substrate and target: 190mm
[0063] (Carbon layer deposition conditions) Target film thickness: 150 nm Processing temperature: 140℃ Sputtering gas pressure: 0.5Pa Sputtering gas (input gas): Ar Sputtering gas flow rate: 380sccm Voltage value: -250V Frequency: 40kHz C cathode output: 80A Orbital speed: 4.0 rpm
[0064] [Example 2] A separator E2 was produced in the same manner as in Example 1, except that the bias voltage was set to -200V.
[0065] [Example 3] A separator E3 was produced in the same manner as in Example 1, except that the bias voltage was set to -300V.
[0066] [Comparative Example 1] A separator C1 was produced in the same manner as in Example 1, except that the bias voltage was set to 0V.
[0067] [Comparative Example 2] Separator C2 was produced in the same manner as in Example 1, except that the sputtering gas pressure was set to 2.5 Pa by adjusting the flow rate of the sputtering gas.
[0068] [Comparative Example 3] Separator C3 was produced in the same manner as in Example 1, except that the sputtering gas pressure was set to 5.0 Pa by adjusting the flow rate of the sputtering gas.
[0069] [evaluation] (ratio of film thickness between convex and concave parts) For the obtained separators E1 to E3 and C1 to C3, the thickness of the titanium layer at the convex and concave portions was measured, and the thickness ratio was calculated. The thickness of the titanium layer was measured at least 10 points on the tops of the convex portions and the bottoms of the concave portions in an SEM photograph of the separator cross section, and the thickness was calculated as the average value. The results are shown in Table 1 below.
[0070] (Titanium layer structure) For the obtained separators E1 to E3 and C1 to C3, the cross section of the titanium layer was observed by SEM to confirm the structure. The results are shown in Table 1 below. Fig. 4 shows an SEM photograph of the cross section of separator E1 according to Example 1. Fig. 5 shows an SEM photograph of the cross section of separator C1 according to Comparative Example 1.
[0071] [Table 1]
[0072] From the above results, it was confirmed that the manufacturing method according to this embodiment can increase the film thickness ratio of the convex portion to the concave portion, particularly the film thickness ratio can be increased to 0.80 or more. It was also confirmed that the manufacturing method according to this embodiment can obtain a titanium layer having a flat structure. Specifically, as shown in FIG. 4, the titanium layer formed in the example had a flat structure in which there was no boundary or gap leading from the titanium layer surface to the metal substrate surface, as seen in the columnar structure. This flat structure has excellent corrosion resistance because there is no boundary or gap leading to the metal substrate surface. On the other hand, as shown in FIG. 5, the titanium layer formed in the comparative example had a columnar structure, and there was a boundary or gap leading from the titanium layer surface to the metal substrate surface.
[0073] The upper limit and / or lower limit of the numerical ranges described in this specification can be arbitrarily combined to define a preferred range. For example, the upper limit and lower limit of the numerical range can be arbitrarily combined to define a preferred range, the upper limit of the numerical range can be arbitrarily combined to define a preferred range, and the lower limit of the numerical range can be arbitrarily combined to define a preferred range.
[0074] Although the present embodiment has been described in detail above, the specific configuration is not limited to this embodiment, and even if there are design changes within the scope that does not deviate from the gist of this disclosure, they are included in this disclosure. [Explanation of symbols]
[0075] 1: Cell 2:MEGA 3: Separator 4: Membrane electrode assembly (MEA) 5: Electrolyte membrane 6: Electrode 7: Gas diffusion layer 10: Fuel cell 21: Gas flow path 22: Gas flow path 23: Coolant channel 101: Metal base material 101a: Metal base material 101b: Metal base material 102: Titanium layer 103: Carbon layer 1001: Fuel cell separator 1002: Fuel cell separator
Claims
1. A method for manufacturing a fuel cell separator having a titanium layer made of titanium on a metal substrate having an uneven flow channel shape, comprising the steps of: The method includes the step of depositing a titanium layer on a metal substrate by a sputtering method in which a negative bias voltage is applied to the metal substrate; The sputtering gas pressure is 0.5 Pa or less, The manufacturing method, wherein the negative bias voltage is 150V or more.
2. The method according to claim 1 , wherein the negative bias voltage is 150 V or more and 1280 V or less.
3. 3. The method according to claim 1, wherein the negative bias voltage is 150 V or more and 500 V or less.
4. The method according to any one of claims 1 to 3, wherein sputtering is carried out using a sputtering target containing titanium as a main component.
5. The method according to any one of claims 1 to 4, wherein argon is used as the sputtering gas.
6. The method according to any one of claims 1 to 5, wherein the formed titanium layer has a flat structure, and no boundary or gap exists between the surface of the titanium layer and the surface of the metal substrate.
7. The method according to any one of claims 1 to 6, wherein a ratio (B / A) of a thickness A of the titanium layer formed on the protruding portions of the metal substrate to a thickness B of the titanium layer formed on the recessed portions is 0.8 or more.
8. The method according to any one of claims 1 to 7, wherein the metal substrate is a stainless steel substrate.
9. The method according to any one of claims 1 to 8, further comprising the step of depositing a carbon layer made of carbon on the deposited titanium layer.
Citation Information
Patent Citations
Separator for solid electrolyte fuel cell, its manufacture, and solid electrolyte fuel cell
JP1998270062A
Manufacturing method of fuel cell separator
JP2006286457A
Manufacturing method for fuel cell separator
JP2008034113A
Conductive member, manufacturing method thereof, as well as fuel cell separator and solid polymer fuel cell using the same
JP2010153353A
Ball joint and method of manufacturing the same
JP2014211190A